THE ROLE AND IMPORTANCE OF DOYRA PLAYER IN UZBEK MUISIQA PERFORMANCE - Bakirov Abbas Akrom son (Galaxy International Interdisciplinary Research Journal, 2022)
This article discusses the historical development, form, structure and role of the doyra, one of the Uzbek folk instruments, in the performance of national music.